Managing services marketing : text and readings - Bateson, John E.G.; Hoffman, K. Douglas (Fort Worth : The Dryden Press / Harcourt Brace College Publishers, 1999)
Business
2004-07-26
Keywords: Marketing; Managing serices; SErvice consumer; Service operation; Communication strategy; Defection management